Properties and stochastic nature of BEA's early estimates of GNP - Neftci, Salih; Theodossiou, Panayiotis (My University, 1991)
In this article we investigate the extent to which successive estimates of the GNP prepared by the Bureau of Economic Analysis “fully” reflect available information. Using a statistical framework based on the properties of nested information sets and recursive projection, we have derived and tested specific restrictions these estimates should follow. The tests carried out show that all preliminary estimates fail to meet the restrictions
Keywords: Business; Economics; Capital market; Finance--Statistics